plz solve this step by step plz help me for my exam
Attachments:
![](https://hi-static.z-dn.net/files/d6c/8b464cc31de5fc8967eda0b73c5c10ef.jpg)
Answers
Answered by
3
✨✨
7) p = 1/5
8) 16a²+4b²+9c²-16ab-12bc-24ac
✨✨
The answer is in picture ✅✅
Attachments:
![](https://hi-static.z-dn.net/files/d91/dce97d9358037137622c5a65a8b14748.jpg)
![](https://hi-static.z-dn.net/files/dc4/fd0c641a5a61c4b9c52c52cffb09813d.jpg)
Answered by
1
Answer:
Step-by-step explanation:
7. (36x² - p²) = (6x + 1/5) ( 6x- 1/5)
⇒ (36x² - p²) = (6x)² - (1/5)² applying (a+b) (a-b) = a² - b²
⇒36x² - p² = 36x² - (1/5)²
Equating corresponding terms
we can say p² = (1/5)²
⇒ p = 1/5
8. (4a-2b-3c)²
=[ (4a-2b) - (3c)]²
applying ( x-y) ² = x² + y² - 2xy
= (4a - 2b)² + (3c)² - 2 ( 4a - 2b) (3c)
= [ (4a)² + (2b)² - 2 ( 4a) (2b) ] + 9c² - 2 ( 12ac - 6bc)
= 16a² + 4b² - 16ab + 9c² - 24 ac + 12bc
= 16a² + 4b² +9c² - 16ab + 12bc - 24ac
Similar questions